Electrochemical immunosensor for detection of CA 15-3 biomarker in point-of-care - Rebelo, Tânia S.C.R. (2021)
This work reports the development of a simple and rapid electrochemical immunosensor for the determination of breast cancer biomarker Cancer Antigen 15–3 (CA 15–3). Disposable and cost-effective chips, consisting of gold screen-printed electrodes (AuSPEs), were used to develop the portable electrochemical devices for monitoring the biomarker in point-of-care (PoC), under clinical context. The biosensor preparation consisted of two simple steps. First, a self-assembled monolayer (SAM) of mer-captosuccinic acid (MSA) was formed at the AuSPE surface. Then, the CA 15–3 antibody was covalently bound to the carboxylic groups standing at the electrode surface using EDC/NHS chemistry. The performance of the developed immunosensor was evaluated by assessing the sensor sensitivity, linear response interval, selectivity and detection limit (LOD). The developed immunosensor provided a wide linear concentration range (from 1.0 to 1000 U mL